Adaptive School Management in Facing Technological Disruption in Elementary Schools in Mataram - Usman Jayadi (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze Adaptive School Management in Facing Technological Disruption in Elementary Schools in Mataram. The focus of this study is to examine the implementation of adaptive school management, the principal's strategy in managing digital transformation, supporting and inhibiting factors, and their implications for improving the quality of education. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that the implementation of adaptive school management in elementary schools in Mataram City is carried out through the transformation of the principal's adaptive leadership, digitalization of school administration, strengthening an innovative organizational culture, improving teachers' digital competence, and collaboration with educational stakeholders. The principal's strategy in managing change is carried out through digital vision-based leadership, data-driven decision-making, and strengthening human resource capacity. The main supporting factors include education policy, infrastructure support, and teacher competence, while inhibiting factors include the digital literacy gap and resistance to change. The implications of this study indicate that adaptive school management can improve the effectiveness of governance, the quality of learning, and the quality of education sustainably in the era of technological disruption. This study concludes that adaptive school management is an important strategic approach in increasing the adaptability of elementary schools to technological change.